Theory Characteristics of the Features of Law that Express its Positive Essence - LUTSKYI, Andriy I.; LUTSKYI, Myroslav I.; LUTSKYI, Roman P. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).27, 2020)
Nowadays, scientific thought pays little attention to coverage of the essence of such features of law as systematicity and universality. They are the ones that cover the internal structure of appointment and the role of such a category as ‘positive law’. The essential features of positive law reflect the central formula of this category, which reflects the quintessence of the concept of ‘law’. The term ‘positive law’ means a rule of conduct that is accepted and sanctioned by the state and is universally binding. The purpose of the paper is to determine the essence and features of positive law based on a correct understanding of the features that describe this phenomenon, as well as are key factors in legal consciousness. The essential features of positive law presented in the paper reflect the central formula of this category, which reflects the quintessence of the concept of ‘law’; this formula can be supplemented and modified, but it cannot be left out without compromising the full coverage of the content, structure, and mechanism of law.